Biodiversity and relationship between biomass of epiphytic macroalgae and habitat in Sibuti mangrove, Sarawak, Malaysia - Md Isa, Hasmidah (2016)
Mangrove macroalgal species is considered to be an important marine and brackish water plant that supports diversely in coastal and estuarine ecosystems. They provide nutrients to the primary consumers in the aquatic food web, and reported to be a substantial contributor in the coastal and marine ecosystems. This study was aimed to investigate the epiphytic macroalgal species, and their biomass and habitat characteristics in Sibuti mangrove forest, Sarawak, Malaysia. A total of eight species of mangrove macroalgae were recored and identified from this estuarine forest ecosystems. The abundance of macroalgal species was higher in the mouth of the river (Station 1) compared to the middle (Station 2) and upper estuary (Station 3). Three groups of mangrove macroalgae were identified, in which 5 species were from Rhodophyta (Caloglossa ogasawaraensis, Caloglossa adhaerens, Caloglossa stipitata, Bostrychia anomala and Hypnea sp.), 2 species were from Chllorophyta (Chaetomorpha minima and Chaetomorpha sp.) and 1 species was from Phaeophyta (Dictyota sp.). The Bostrychia anomala and Caloglossa adhaerens species were the first distributional record of mangrove macroalgae in Malaysian coastal waters. Macroalgal diversity and biomass were influenced by habitats namely nutrient concentrations of water, tidal level, turbidity, salinity and soil characteristics in this mangrove forest. Macroalgal biomass was higher in Station 1 (246.64 mg/cm²) followed by Station 3 (240.18 mg/cm²) and Station 2 (144.29 mg/cm²). Macroalgae Hypnea sp. was hardy and it can survive and withstand in fluctuated environment in the estuarine habitats and found be grown in all stations during the study period. The finding of this study suggests for further investigation of macroalgal diversity in other mangrove forests in Sarawak to identify the suitable species for biodiversity conservation, culture development, biomonitoring and bioindicator purposes. It is also aspected that macroalgae as an ecosystem indicator species, the finding of the study would help to detect and manage the healthy mangrove ecosystems in Malaysian waters.